Analysis of Technical Inefficiency in Rice Production among Farmers in Ezza South LGA of Ebonyi State of Nigeria (Application of Stochastic Frontier Production) - , Ume Smiles Ifeanyichukwu, Ezeano Caleb Ike, Eluwa Akubuike N, Ebe Felix (Archives of Current Research International, 2016)
This study mainly measure the level of technical inefficiency and the determinants factors among rice farmers in Ezza south of Ebonyi State, Nigeria using stochastic frontier production function. Multi- stage random sampling technique was used to select 120 rice farmers from which input and output data were collected. The instruments of data collection were well structured and pretested questionnaire and oral interview. The estimated farmers’ levels of technical inefficiency ranged from between 0.24 and 0.98 with mean technical inefficiency of 0.56. The determinants of technical inefficiency in rice production in the study area were farming experience and household size. The limiting factors to rice production in the study area were high cost of improve inputs, poor access to credit, poor access to information and problem of diseases and pests. High technical efficiency could be attained through efficient allocation of the employed resources which is vital to rice green revolution in the study area in particularly and the country in general. Furthermore, there is need to enhance both old and new entrant farmers’ productivity through adequate access to improved production inputs.